(untitled) (Proceedings of Southern Federal University. Philology, 2020)
The article examines the specificity of the artistic time and space of V. Borisov’s poetry «Shortening the parting» (2018). The purpose of the study is to identify the features of the spatio-temporal organization and semantics of the frame elements. During the research, textological and hermeneutic methods were implied. The book’s architectonics is based on the opposition of spatial and temporal forms. Such a construction is directly related to the semantics of poetry and the formation of a certain picture of the world of Borisov, whose lyrical character overcomes loneliness. The name of each poem is not only a reference to a specific source, but also a «key» important for understanding the underlying meaning (an indication of a fact or event). Seven color illustrations introduced into the collection make it possible to combine two types of art, and the poet to make his poems «visible» and create a chronicle of the main events. Contrasting in the collection near and far (city and village), closed and open (room and street) spaces, both in texts and in illustrations, V. Borisov focuses on the feelings the protagonist experiences when he is forced to gradually overcome loneliness. The season depicted in the figures is summer, the semantics and images of which appear throughout the collection and which is often contrasted with winter paintings. The main topos, where events unfold, appears to be Moscow as a city that “absorbed” the features of Dostoevsky’s Petersburg. The space of the capital appears as an alien to the lyrical character, who is forced to «wade through traffic, advertising, movie trailers.» Physical or cyclical time is either stated specifically («today»), or is present in allegorical images with accompanying motives. The effect of «slowed down» time can be achieved not only by the lack of indication of dates, but also by attachment to generally accepted or national events. Various spatial and temporal forms are presented in the book of poems «Shortening the Parting» by V. Borisov, which testifies to the complex organization of the collection and the author’s intention. Key words: time, space, «Shortening the Parting», Veniamin Borisov, chronotope, frame elements. DOI 10.18522/1995-0640-2020-4-158-168